1982
DOI: 10.2527/jas1982.55128x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Nutritional Status of Beef Cattle Herds from Four Soil Order Regions of Florida. I. Macroelements, Protein, Carotene, Vitamins A and E, Hemoglobin and Hematocrit

Abstract: The nutrient status of grazing beef cattle from four selected soil order regions of Florida was examined. Liver, blood, hair and feces samples from 14 heifers and 14 cows, plus forage samples, were collected during two periods of the year from nine ranches located in four different regions. Soil samples were collected during one period. The soil order regions were the Histosol (southeast), Spodosol (southwest), Entisol (central) and Ultisol (northwest). Mean forage P values were higher (P less than .05) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Mineral deficiencies are often "area" problems. Nevertheless, the study reported herein, and the companion paper (Kiatoko et al, 1982) indicated that P, Se and Zn deficiencies were present in all of the four regions studied. Protein, vitamin A, K, Mg, Na, Cu and Co deficiencies were found in certain regions and were related to season of the year.…”
Section: Conclusion Related To Trace Element Statusmentioning
confidence: 40%
See 3 more Smart Citations
“…Mineral deficiencies are often "area" problems. Nevertheless, the study reported herein, and the companion paper (Kiatoko et al, 1982) indicated that P, Se and Zn deficiencies were present in all of the four regions studied. Protein, vitamin A, K, Mg, Na, Cu and Co deficiencies were found in certain regions and were related to season of the year.…”
Section: Conclusion Related To Trace Element Statusmentioning
confidence: 40%
“…1, 1982 by on October 28, 2010. jas.fass.org Downloaded from soil type regions. Nutritional status of the macroelements, vitamin A and protein were reported in the previous article (Kiatoko et al, 1982); the present paper evaluated the trace minerals.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, some studies showed that cattle maintain fairly normal electrolyte balances and others showed either no marked changes in plasma Na, K (Blincoc and Brody, 1951) and Ca (Kamal and Abdelaal, 1972;Shafferi et al, 1981;Kiatoko et al, 1982) or significant increase in plasma P (Kamal and Abdelaal, 1972) and serum Na, K and Ca (Shebaita and Pfau, 1982), under heat stress conditions. These different effects may be due to the difference in availability of diets rich in particular minerals.…”
Section: Mineral Intakementioning
confidence: 96%